Fertility life table of Trichogramma pretiosum and Trichogramma acacioi (Hymenoptera: Trichogrammatidae) on Sitotroga cerealella (Lepidoptera: Gelechiidae) eggs at different constant temperatures - Pratissoli, D.; Fernandes, O. A. [UNESP]; Zanuncio, J. C.; Pastori, P. L. (My University, 2004)
Fertility life tables were developed for both Trichogramma pretiosum and Trichogramma acacioi reared on Sitotroga cerealella eggs as an alternative host at five different temperatures. The egg parasitoids were first collected from Nipteria panacea eggs, a lepidopterous pest of avocado. Egg parasitoid females were individualized in small glass vials along with 40 eggs of the host during 24 h for parasitization. For evaluation of the parasitism capacity, a similar procedure was adopted, but cardboards with eggs were replaced every day. The net reproductive rate (Ro), intrinsic rate of increase (rm), finite rate of increase (λ), and mean generation time (T) were estimated. Temperature affected all parameters for both Trichogramma species. The highest fecundity for both species was observed at 25°C. Extreme temperatures such as 15°C or 35°C negatively affect the development rate of both species. © 2004 Entomological Society of America.
Keywords: Alternative host; Egg parasitoids; Life history; Trichogramma acacioi; Trichogramma pretiosum